Express lane meals : what to keep on hand, what to buy fresh for the easiest-ever 30-minute meals - Ray, Rachael. frey50 (New York : Clarkson Potter Publishers, 2006)
How can you get a wholesome, delicious dinner on the table without spending time on long lines at the supermarket? Rachael knows how! Her secret weapon is keeping plenty of versatile, flavorful ingredients in the cupboard, fridge, and freezer, combining these staples with just a few fresh items-never more then ten--to create delicious meals for every night of the week. In Express Lane Meals, Rachael provides her personal go-to list of must-have items-so you can do a big shop every week then simply zip through the Express Lane to make any of these 30-minute meals. She divides the recipes into three categories: "Meals for the Exhausted," "Meals for the Not Too Tired," and "Bring It On! (But, Be Gentle)." No matter which you choose you'll learn handy tricks and shortcuts to get the most impressive-looking meals on the table in 30 minutes or less. These are Rachael's quickest and easiest recipes yet and a breeze to shop for-because you shouldn't have to spend all of the time Rachael saves you in the kitchen standing in line at the grocery store!
Keep in on hand : the master list of what to buy, how much to keep around and where to store it -- Meals for the exhausted -- Meals for the not too tired -- Bring it on! (but, be gentle) -- Index -- Express lane shopping lists.
Includes index.
At head of title: Rachael Ray.
Keywords: Quick and easy cookery